2017
DOI: 10.1002/jbm.a.36004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of osteogenic activity by regulation of WNT and BMP signaling during titanium particle induced osteolysis

Abstract: Periprosthetic osteolysis remains the leading obstacle for total joint replacements. Primarily, it was thought that aseptic loosening is mainly caused by macrophage mediated inflammatory process arising from production of wear debris. The role of osteoclasts and its sequential bone resorption ability has been extensively studied, but little is known about impaired osteogenesis during osteolysis. In the current study, we have tried to delineate the regulatory mechanism of osteogenic signals by Ti particles in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Osteogenic differentiation and mineralization of osteoblasts are also impaired on exposure to wear particles. These effects are evidenced by the reduced gene expression of early boneformation-associated genes [e.g., ALP, runx 2, osterix (Dean et al, 1999a;Lohmann et al, 2000;Shen et al, 2014;Gu et al, 2017)] and late osteogenic markers (e.g., osteocalcin) (Nam et al, 2017), whilst simultaneously losing their capacity to synthesize type I collagen (Allen et al, 1997;Yao et al, 1997;Vermes et al, 2000Vermes et al, , 2001Lochner et al, 2011;Schulze et al, 2013) and mediate mineralization (Gu et al, 2017). Additionally, similar trends were observed in the expression of osteoblastogenesisrelated transcription factors such as osteopontin (OPN), TGF-β1, sp7, bgalp, Fra-2 (fos related antigen-2), Dlx5, and Dkk1 (dickkopf-related protein 1), even though some of these trends were not statistically significant (Chiu et al, 2010;Ma et al, 2010;Shen et al, 2014;Sun et al, 2015;Deng et al, 2017b;Gu et al, 2017).…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteogenic differentiation and mineralization of osteoblasts are also impaired on exposure to wear particles. These effects are evidenced by the reduced gene expression of early boneformation-associated genes [e.g., ALP, runx 2, osterix (Dean et al, 1999a;Lohmann et al, 2000;Shen et al, 2014;Gu et al, 2017)] and late osteogenic markers (e.g., osteocalcin) (Nam et al, 2017), whilst simultaneously losing their capacity to synthesize type I collagen (Allen et al, 1997;Yao et al, 1997;Vermes et al, 2000Vermes et al, , 2001Lochner et al, 2011;Schulze et al, 2013) and mediate mineralization (Gu et al, 2017). Additionally, similar trends were observed in the expression of osteoblastogenesisrelated transcription factors such as osteopontin (OPN), TGF-β1, sp7, bgalp, Fra-2 (fos related antigen-2), Dlx5, and Dkk1 (dickkopf-related protein 1), even though some of these trends were not statistically significant (Chiu et al, 2010;Ma et al, 2010;Shen et al, 2014;Sun et al, 2015;Deng et al, 2017b;Gu et al, 2017).…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…In parallel, the expression of negative regulators of osteogenesis, such as BMP3, sclerostin (SOST), and Msx2, is found to be temporarily up-regulated during osteogenesis (Chiu et al, 2010;Ma et al, 2010). The particle-induced inhibition of osteogenic differentiation is mainly mediated by Wnt/β-catenin and BMP/smad signaling pathways, as both BMP and WNT signaling were suppressed in osteoprogenitor cells (Sun et al, 2015;Nam et al, 2017;Sun et al, 2019). Thus, these two signaling pathways could be used as a potential therapeutic target.…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…Production of titanium (Ti), ultra-high molecular weight polyethylene (UHMWPE), or cement wear debris following TJA is deemed to play a critical role in the process of osteolysis ( Noordin and Masri, 2012 ). Considerable studies have shown that chronic inflammatory response and increased osteoclast-related bone resorption, which occur in response to implant-derived wear debris, might be responsible for osteolysis ( Masui et al, 2005 ; Holding et al, 2006 ; Abu-Amer et al, 2007 ; Nam et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no activation of p38 MAPK was not observed in SW982 cells (Figure 3). Likewise, no activation of p38 by Ti particles has been reported in osteoblasts [36]. It appears that p38 signaling activation depends on the cell type, which might be essential for osteoclasts and macrophages, contributing to the inflammatory osteolysis.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of MAPKs by wear particles is associated with induced inflammatory responses in various cell types [36][37][38]. Wear debris has been shown to stimulate intracellular signaling pathways such as MAPKs, leading to the secretion of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%